Within-Subject Comparison of Word Recognition and Spiral Ganglion Cell Count in Bilateral Cochlear Implant Recipients - Seyyedi, Mohammad (2014)
OBJECTIVES: Although published reports have not demonstrated a positive correlation between the number of residual spiral ganglion cells (SGC) and word recognition scores in patients with unilateral multichannel cochlear implants, this study was designed to retest this hypothesis in patients with bilateral multichannel cochlear implants. MATERIALS AND METHODS: From a pool of 133 temporal bones, all subjects with bilateral multichannel cochlear implants who were deafened bilaterally by the same etiology were studied. A total of 12 temporal bones from 6 subjects were identified and processed after death for histology. The SGCs were counted by standard techniques. The differences between left and right SGC counts as well as the differences in word recognition scores were calculated for each subject. Correlation analysis was performed between the differences of SGC counts and the differences of word recognition scores. RESULTS: Differences in SGC counts were highly correlated with the differences in word recognition scores (R=0.934, P-value= 0.006). CONCLUSION: This study suggests higher residual SGCs predicted better performance after implantation in a given patient. The results also support attempts to identify factors which may promote survival of SGCs.